Case report: Acute audiovestibular presentation following hemi-pontine infarction - Koohi, Nehzat; Haider, Salman; Kharytaniuk, Natallia; Werring, David J; Bamiou, Doris-Eva; Kaski, Diego (Frontiers in Stroke, 2023)
Posterior circula3on stroke is an uncommon cause for sudden-onset sensorineural hearing loss (SSNHL). The anterior inferior cerebellar artery occlusion results in ipsilateral peripheral audioves3bular dysfunc3on. Few reports describe posterior circula3on stroke presen3ng with contralateral SSNHL and acute ves3bular and focal neurological signs. We present a case of contralateral SSNHL and isolated acute central ves3bular dysfunc3on in the absence of other central focal neurological deficits. To the best of our knowledge, this has not been described to-date. The pa3ent was iden3fied to have asymmetrical SSNHL, subtle skew devia3on with lef head-3lt, lef gaze-evoked nystagmus, significant refixa3on-saccades on video head-impulse test despite bilaterally normal ves3bulo-ocular reflex gains. Lef pon3ne infarct was suspected and confirmed on MRI. The pa3ent was treated with appropriate an3platelet regimen. We highlight the importance of a thorough clinical diagnos3c work-up as posterior circula3on strokes with isolated audioves3bular deficits can be easily missed if other significant neurological deficits are absent.